Encapsulating polymer and method of preparation, electrode for a sulfide solid-state battery, battery
Patent Information
- Application Number
- CN202611082657.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]本发明的目的在于针对现有技术中存在的问题,提供一种封装用聚合物及制备方法、硫化物固态电池用电芯、电池;通过特定反应单体聚合得到的聚合物链段,具有良好的柔顺性、疏水性与化学稳定性,通过氯化改性在聚合物链段上引入强极性基团进一步增强其与集流体的附着力;解决了将其用于硫化物固态电池中,与集流体附着力不佳或者电池电化学性能不佳的问题
本发明通过对聚合物结构的设计,异丁烯和含乙烯基锂盐化合物聚合后,生成含锂离子的共聚物链段,此链段被赋予了良好的柔顺性、疏水性与化学稳定性;将其用于硫化物固态电池中避免了正负极直接接触而产生的消耗锂的副反应发生,有效提升了硫化物固态电池的循环性能。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to polymers for encapsulation and their preparation methods, cells for sulfide solid-state batteries, and batteries. Background Technology
[0002] With technological advancements and ever-increasing demands for battery energy density and safety, solid-state batteries, especially lithium-ion batteries using sulfide solid electrolytes, are considered a crucial next-generation technology. Sulfide solid electrolytes typically exist as particles and cannot form a continuous insulating layer on the sides of the cell like a flexible separator. This leads to a risk of internal short circuits caused by direct contact between the positive and negative electrodes at the edges after battery stacking.
[0003] Currently, coating the side of the battery cell with an insulating adhesive can improve the risk of short circuits. However, this method also has certain limitations. For example, the adhesive may not adhere well to the current collector, or the insulation may be damaged during static pressure processing such as battery manufacturing. This can limit the electrochemical performance of the battery or the yield and safety of battery production.
[0004] Therefore, developing a material that can be effectively used for the side insulation encapsulation of sulfide solid-state battery cells has become a very important research topic.
[0005] In view of this, the present invention is hereby proposed. Summary of the Invention
[0006] The purpose of this invention is to address the problems existing in the prior art by providing a polymer for encapsulation and a preparation method thereof, a cell for a sulfide solid-state battery, and a battery. The polymer segments obtained by polymerization of specific reactive monomers have good flexibility, hydrophobicity, and chemical stability. The adhesion between the polymer segments and the current collector is further enhanced by introducing strongly polar groups on the polymer segments through chlorination modification. This solves the problem of poor adhesion to the current collector or poor electrochemical performance of the battery when used in sulfide solid-state batteries.
[0007] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a polymer for encapsulation, which is obtained by polymerizing reactive monomers and then modifying them with chlorination; The reaction monomers include isobutylene and vinyl lithium salt compounds.
[0008] Furthermore, the vinyl lithium salt compound includes lithium styrene sulfonate and / or lithium vinyl sulfonate.
[0009] Furthermore, it includes at least one of the following features (1) to (4); (1) The mass ratio of the lithium styrene sulfonate to the lithium vinyl sulfonate is 1:(0.2~2); (2) The mass of the isobutylene accounts for 80% to 90% of the mass of the reactant monomer; (3) The mass of the lithium styrene sulfonate accounts for 1% to 10% of the mass of the reactant monomer; (4) The mass of the lithium vinyl sulfonate accounts for 1% to 10% of the mass of the reactant monomer.
[0010] Furthermore, the chlorination modification includes modification treatment with a chlorinating agent; the chlorinating agent includes chlorine gas.
[0011] Secondly, the present invention also provides a method for preparing the encapsulation polymer as described above, comprising the following steps: The reactive monomers are mixed and polymerized. After the polymerization reaction is completed, post-treatment is performed, followed by chlorination modification to obtain the encapsulation polymer.
[0012] Furthermore, the polymerization reaction is carried out at a pressure of 0.5~1.5MPa and a temperature of 50~70℃.
[0013] Furthermore, the reaction conditions for the chlorination modification are: pressure of 0.05~0.3MPa, temperature of 35~45℃, and time of 10~30min.
[0014] Thirdly, the present invention also provides a cell for a sulfide solid-state battery, which is obtained by coating the side of the cell with a packaging polymer prepared by the packaging polymer as described above or by the packaging polymer preparation method described above.
[0015] Furthermore, the polymer coating for encapsulation is prepared as a polymer solution with a mass concentration of 1% to 3%.
[0016] Fourthly, the present invention also provides a sulfide solid-state battery, including the sulfide solid-state battery cell described above.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention designs a polymer structure that polymerizes isobutylene and a vinyl lithium salt compound to generate a lithium-ion-containing copolymer segment. This segment is endowed with good flexibility, hydrophobicity, and chemical stability. When used in sulfide solid-state batteries, it avoids the side reaction that consumes lithium caused by direct contact between the positive and negative electrodes, effectively improving the cycle performance of sulfide solid-state batteries.
[0018] After chlorination modification, the polymer of the present invention introduces strongly polar groups into the molecular chain, which enables it to adhere firmly to the current collector inside the battery, such as a metal current collector. This can prevent the polymer from peeling off from the edge of the electrode in sulfide solid-state batteries under isostatic high-pressure conditions or during long-term use, thus ensuring the long-lasting reliability of the polymer's insulation protection for the battery.
[0019] The encapsulation polymer provided by this invention is specifically designed for the manufacturing process of sulfide solid-state batteries, especially the isostatic pressing process. Its rheological properties and curing behavior can perfectly match the requirements of existing production lines, significantly improving the yield and safety of battery production. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained from these drawings without creative effort.
[0021] Figure 1 This is an optical microscope image of the cell edge before coating in Embodiment 1 of the present invention.
[0022] Figure 2 This is an optical microscope image of the edge of the coated battery cell according to Embodiment 1 of the present invention.
[0023] Figure 3 The image shows the infrared spectrum of the encapsulation polymer prepared in Example 1 of this invention. Detailed Implementation
[0024] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0025] In some embodiments of the present invention, a polymer for encapsulation is provided, which is obtained by polymerizing reactive monomers and then modifying them with chlorination; The reaction monomers include isobutylene and vinyl lithium salt compounds.
[0026] This invention designs a polymer structure by polymerizing isobutylene and a vinyl lithium salt compound to generate a lithium-ion-containing copolymer polymer segment. The isobutylene unit serves as the main structural framework, endowing the polymer segment with good flexibility, hydrophobicity, and chemical stability, which helps to improve the initial flowability of the polymer and the mechanical toughness after film formation. When this polymer is used in sulfide solid-state batteries, it avoids the side reaction of lithium consumption caused by direct contact between the positive and negative electrodes, effectively improving the cycle performance of the battery.
[0027] After chlorination modification, the polymer of the present invention introduces strongly polar groups into the polymer chain segments, which can further enhance its adhesion to the current collector, such as the metal current collector, and significantly improve the peel strength of the polymer-metal interface, so that it can form a firm adhesion with the metal current collector inside the battery. This can prevent the polymer from peeling off from the edge of the electrode in the sulfide solid battery under isostatic high pressure environment or during long-term use, and ensure the long-term reliability of the polymer's insulation protection for the battery. This provides the possibility of applying it to solid batteries to ensure the yield and safety of battery production.
[0028] In some embodiments of the present invention, the vinyl lithium salt compound includes lithium styrene sulfonate and / or lithium vinyl sulfonate; preferably, the vinyl lithium salt compound includes lithium styrene sulfonate and lithium vinyl sulfonate.
[0029] Taking lithium styrene sulfonate as an example, the highly active monomer of lithium styrene sulfonate is used as a bridge to form active species through free radical initiators (such as ammonium persulfate), thereby inducing isobutylene to participate in copolymerization and form stable copolymer segments.
[0030] In some embodiments of the present invention, the mass ratio of lithium styrene sulfonate to lithium vinyl sulfonate is 1:(0.2~2); typically, but not limitingly, for example, the mass ratio of lithium styrene sulfonate to lithium vinyl sulfonate can be 1:0.2, 1:0.5, 1:1, 1:1.5 or 1:2, etc., and of course any value within the above range is also possible, without specific limitation here.
[0031] In some embodiments of the present invention, the mass of isobutylene accounts for 80% to 90% of the mass of the reactant monomers; typically, but not limitingly, for example, the mass of isobutylene accounts for 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, or 90% of the mass of the reactant monomers, etc., and of course, any value within the above range is also possible, without specific limitation here.
[0032] In some embodiments of the present invention, the mass of lithium styrene sulfonate accounts for 1% to 10% of the mass of the reactant monomer; typically, but not limitingly, for example, the mass of lithium styrene sulfonate accounts for 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% of the mass of the reactant monomer, etc., and of course, any value within the above range is also possible, without specific limitation here.
[0033] In some embodiments of the present invention, the mass of lithium vinyl sulfonate accounts for 1% to 10% of the mass of the reactant monomer; typically, but not limitingly, for example, the mass of lithium vinyl sulfonate accounts for 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% of the mass of the reactant monomer, etc., and of course, any value within the above range is also possible, without specific limitation here.
[0034] In some embodiments of the present invention, the reactive monomers undergo polymerization after being initiated by an initiator; preferably, the initiator includes a thermal initiator; more preferably, the thermal initiator includes potassium persulfate and / or ammonium persulfate; even more preferably, the initiator includes ammonium persulfate.
[0035] In some embodiments of the present invention, polymerization is carried out in an aqueous emulsion system; the aqueous emulsion system includes water and an emulsifier, the emulsifier including anionic emulsifiers; preferably, the anionic emulsifier includes at least one selected from fatty acid salts, alkyl sulfates, alkyl sulfonates and alkyl aryl sulfonates.
[0036] In some embodiments of the present invention, fatty acid salts include, but are not limited to, sodium fatty acid salts; alkyl sulfates include, but are not limited to, sodium alkyl sulfates; alkyl sulfonates include, but are not limited to, sodium alkyl sulfonates; alkyl aryl sulfonates include, but are not limited to, sodium alkyl aryl sulfonates; preferably, the emulsifier includes sodium dodecyl sulfonate and / or sodium dodecyl sulfate.
[0037] In some embodiments of the present invention, chlorination modification includes treatment with a chlorinating agent; the chlorinating agent includes chlorine gas.
[0038] In some embodiments of the present invention, a method for preparing a polymer for encapsulation is also provided, comprising the following steps: The reactive monomers are mixed and polymerized. After the polymerization is completed, post-treatment is performed, followed by chlorination modification to obtain the polymer for encapsulation.
[0039] In some embodiments of the present invention, the polymerization reaction pressure is 0.5~1.5MPa and the temperature is 50~70°C; typically, but not limitingly, for example, the polymerization reaction pressure can be 0.5MPa, 0.7MPa, 0.9MPa, 1.1MPa, 1.3MPa or 1.5MPa, etc., and of course, any value within the above range is not specifically limited here; the polymerization reaction temperature can be 50°C, 55°C, 60°C, 65°C or 70°C, etc., and of course, any value within the above range is not specifically limited here.
[0040] In some embodiments of the present invention, the polymerization reaction further includes the addition of an initiator; preferably, the initiator includes a thermal initiator; more preferably, the thermal initiator includes potassium persulfate and / or ammonium persulfate; even more preferably, the initiator includes ammonium persulfate.
[0041] In some embodiments of the present invention, the polymerization reaction is carried out in an aqueous emulsion system; the aqueous emulsion system includes water and an emulsifier, the emulsifier including anionic emulsifiers; preferably, the anionic emulsifier includes at least one of fatty acid salts, alkyl sulfates, alkyl sulfonates and alkyl aryl sulfonates.
[0042] In some embodiments of the present invention, the polymerization reaction specifically includes the following steps: Add a vinyl lithium salt compound, water, emulsifier, and initiator to a polymerization reactor. After evacuating and replacing the nitrogen gas several times, introduce isobutylene to a pressure of 0.5-1 MPa and heat to 50-70°C. When the isobutylene consumption reaches a preset value, stop introducing nitrogen gas. After replacing the nitrogen gas several times, an emulsion is obtained.
[0043] In some embodiments of the present invention, the post-processing includes demulsification and washing; that is, the emulsion obtained from the polymerization reaction is sequentially demulsified and washed with water to obtain the product of the polymerization reaction.
[0044] In some embodiments of the present invention, the reaction conditions for chlorination modification are: pressure of 0.05~0.3MPa, temperature of 35~45℃, and time of 10~30min; typically, but not limitingly, for example, the reaction pressure for chlorination modification can be 0.05MPa, 0.1MPa, 0.15MPa, 0.2MPa, 0.25MPa, or 0.3MPa, etc., or any value within the above range, without specific limitation here; the reaction temperature for chlorination modification can be 35℃, 40℃, or 45℃, etc., or any value within the above range, without specific limitation here; the reaction time for chlorination modification can be 10min, 15min, 20min, 25min, or 30min, etc., or any value within the above range, without specific limitation here.
[0045] In some embodiments of the present invention, chlorination modification specifically includes the following steps: The product of the polymerization reaction is dissolved in an organic solvent, transferred to a pressure vessel, and then a chlorinating agent is introduced into the organic solvent to a pressure of 0.05~0.3MPa. The mixture is heated to 35~45℃ and maintained for 10~30min. After replacing the nitrogen gas, the product is removed, washed with deionized water until neutral, and dried to obtain the polymer for encapsulation.
[0046] In some embodiments of the present invention, a sulfide solid-state battery cell is also provided, which is obtained by coating the side of the cell with the encapsulation polymer prepared by the above-described encapsulation polymer or the above-described encapsulation polymer preparation method.
[0047] The encapsulation polymer provided by this invention is specifically designed for the manufacturing process of sulfide solid-state batteries, especially the isostatic pressing process. Its rheological properties and curing behavior can perfectly match the requirements of existing production lines, significantly improving the yield and safety of battery production.
[0048] In some embodiments of the present invention, the polymer solution for encapsulation is prepared to a mass concentration of 1% to 3% during coating.
[0049] In some embodiments of the present invention, an organic solvent is used to prepare the polymer solution, the organic solvent including at least one of toluene, xylene, butyl butyrate and dichloromethane.
[0050] In some embodiments of the present invention, a sulfide solid-state battery is also provided, including the above-described sulfide solid-state battery cell.
[0051] Example 1 The method for preparing the encapsulation polymer provided in this embodiment includes the following steps: 1g of lithium styrene sulfonate, 1g of lithium vinyl sulfonate, 100g of water, 0.3g of sodium dodecylbenzene sulfonate, and 0.2g of ammonium persulfate were added to a polymerization reactor. After purging with nitrogen three times, isobutylene was introduced to a pressure of 1MPa, and the temperature was raised to 60℃. When the isobutylene consumption reached 10g, the introduction of nitrogen was stopped. After purging with nitrogen three times, the emulsion was removed. The emulsion was demulsified with 10wt% dilute hydrochloric acid and washed three times with water. Then it was dissolved in n-hexane and placed in a pressure vessel. Chlorine gas was introduced into the n-hexane to a pressure of 0.1MPa, and the temperature was raised to 40℃ and maintained for 20min. After purging with nitrogen, the emulsion was removed, washed with deionized water until neutral, and dried to obtain the polymer for encapsulation. Its infrared spectrum is shown below. Figure 3 As shown.
[0052] The method for preparing a sulfide solid-state battery provided in this embodiment includes the following steps: The encapsulation polymer of this embodiment was dissolved in toluene to obtain a polymer solution with a mass concentration of 2%. The polymer solution was then coated onto the side of the stacked sulfide solid-state battery cell, with a coating amount of 0.01~0.05 g / cm³. 2 A sulfide solid-state battery was obtained.
[0053] Example 2 The method for preparing the encapsulation polymer provided in this embodiment includes the following steps: Take 1g of lithium styrene sulfonate, 0.5g of lithium vinyl sulfonate, 100g of water, 0.3g of sodium dodecylbenzene sulfonate, and 0.2g of ammonium persulfate, and add them to a polymerization reactor. After evacuating and replacing the nitrogen gas three times, introduce isobutylene to a pressure of 1MPa and heat to 60℃. When the isobutylene consumption reaches 10g, stop introducing the nitrogen gas. After replacing the nitrogen gas three times, remove the emulsion. Demulsify the emulsion with 10wt% dilute hydrochloric acid and wash it with water three times. Then dissolve it in n-hexane and place it in a pressure vessel. Then introduce chlorine gas into the n-hexane to a pressure of 0.1MPa, heat it to 40℃, maintain it for 20min, replace the nitrogen gas, remove it, wash it with deionized water until neutral, and dry it to obtain the polymer for encapsulation.
[0054] The method for preparing the sulfide solid-state battery provided in this embodiment is the same as in Embodiment 1.
[0055] Example 3 The method for preparing the encapsulation polymer provided in this embodiment includes the following steps: Take 0.5g of lithium styrene sulfonate, 1g of lithium vinyl sulfonate, 100g of water, 0.3g of sodium dodecylbenzene sulfonate, and 0.2g of ammonium persulfate, and add them to a polymerization reactor. After evacuating and replacing the nitrogen gas three times, introduce isobutylene to a pressure of 1MPa and heat to 60℃. When the isobutylene consumption reaches 10g, stop introducing the nitrogen gas. After replacing the nitrogen gas three times, remove the emulsion. Demulsify the emulsion with 10wt% dilute hydrochloric acid and wash it with water three times. Then dissolve it in n-hexane and put it into a pressure vessel. Then introduce chlorine gas into the n-hexane to a pressure of 0.1MPa, heat it to 40℃, maintain it for 20min, replace the nitrogen gas, remove it, wash it with deionized water until neutral, and dry it to obtain the polymer for encapsulation.
[0056] The method for preparing the sulfide solid-state battery provided in this embodiment is the same as in Embodiment 1.
[0057] Example 4 The method for preparing the encapsulation polymer provided in this embodiment includes the following steps: Take 1g of lithium styrene sulfonate, 1g of lithium vinyl sulfonate, 100g of water, 0.3g of sodium dodecylbenzene sulfonate, and 0.2g of ammonium persulfate, and add them to a polymerization reactor. After evacuating and replacing the nitrogen gas three times, introduce isobutylene to a pressure of 1MPa and heat to 60℃. When the isobutylene consumption reaches 10g, stop introducing the nitrogen gas. After replacing the nitrogen gas three times, remove the emulsion. Demulsify the emulsion with 10wt% dilute hydrochloric acid and wash it with water three times. Then dissolve it in n-hexane and put it into a pressure vessel. Then introduce chlorine gas into the n-hexane to a pressure of 0.2MPa, heat it to 40℃, maintain it for 20min, replace the nitrogen gas, remove it, wash it with deionized water until neutral, and dry it to obtain the polymer for encapsulation.
[0058] The method for preparing the sulfide solid-state battery provided in this embodiment is the same as in Embodiment 1.
[0059] Comparative Example 1 The preparation method of the polymer provided in this comparative example is the same as that in Example 1, except that the only monomer used in the reaction is isobutylene, and lithium styrene sulfonate and lithium vinyl sulfonate were not added; no polymer was obtained.
[0060] Comparative Example 2 The preparation method of the polymer provided in this comparative example is the same as that in Example 1, except that no chlorination modification was performed after washing with water; the polymer was obtained by drying after washing with water.
[0061] The preparation method of the sulfide solid-state battery provided in this comparative example is as described in Example 1.
[0062] Comparative Example 3 The polymer provided in this comparative example is CR244 type chloroprene rubber.
[0063] The preparation method of the sulfide solid-state battery provided in this comparative example is as described in Example 1.
[0064] Comparative Example 4 The preparation method of the polymer provided in this comparative example is the same as that in Example 1, except that lithium vinyl sulfonate was not added, that is, the only vinyl lithium salt compound is lithium styrene sulfonate.
[0065] The preparation method of the sulfide solid-state battery provided in this comparative example is as described in Example 1.
[0066] Comparative Example 5 The preparation method of the polymer provided in this comparative example is the same as that in Example 1, except that lithium styrene sulfonate was not added, that is, the vinyl lithium salt compound is only lithium vinyl sulfonate.
[0067] The preparation method of the sulfide solid-state battery provided in this comparative example is as described in Example 1.
[0068] Test case The edge condition of the cell of Example 1 before coating is as shown in Figure 1 shown; the edge condition of the coated cell is as shown in Figure 2 shown.
[0069] The polymers prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were respectively dissolved in toluene to obtain a polymer solution with a mass concentration of 2%, which was then evenly applied onto a single-sided copper foil with a coating thickness of 1 μm. Another layer of copper foil was then covered on top of the polymer, and the surface of the pole piece was rolled back and forth freely with a pressure roller for more than 3 times. The solvent was evaporated by vacuum drying at 80°C, and a long strip-shaped sample piece with a length of 400 mm and a width of 10 mm was cut out. A small section of the copper foil on both sides of the sample was separated, one end was folded 180° and clamped on the upper gripper of a tensile machine, and the other end was clamped on the lower gripper of the tensile machine. The sample was peeled at a stretching speed of 100 mm / min, and the test result of the peel strength was read and recorded in Table 1.
[0070] Table 1
[0071] The sulfide solid-state batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were placed in an isostatic press, the temperature was set to 80°C, the pressure was 120 MPa, and the batteries were taken out after pressing for 20 minutes. The voltage was measured, and a voltage greater than 0.2 V was regarded as qualified. Each battery was tested in parallel 10 times, and the pass rate was recorded in Table 2. Pass rate = number of qualified batteries / total number of tested batteries × 100%.
[0072] Table 2
[0073] The sulfide solid-state batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were charged and discharged at a rate of 0.1 C, with a charge cut-off voltage of 4.3 V, and the obtained charge capacity was recorded as C0; the discharge cut-off voltage was 2.5 V, and the obtained discharge capacity was recorded as C1. The calculation formula of Coulombic efficiency is C1 / C0×100, and the first-cycle Coulombic efficiency results are shown in Table 3.
[0074] Table 3
[0075] It can be seen from Table 1, Table 2 and Table 3 that the present invention adopts the polymerized structure of isobutylene, lithium styrene sulfonate and lithium vinyl sulfonate, and successfully constructs a polymer segment that combines ionic conduction, flexibility, hydrophobicity and chemical stability. Further chlorination modification significantly enhances the interfacial adhesion between the polymer and the metal current collector, and the peel strength is increased up to 36.2 N / m, which has obvious advantages over the comparative examples.
[0076] When the encapsulation polymer of the present invention is applied to a sulfide solid-state battery, the polymer can effectively isolate the positive and negative electrodes, avoid lithium loss side reactions caused by direct contact, and the coulombic efficiency is stable at about 90%. At the same time, its excellent mechanical stability ensures the interface integrity of the battery during manufacturing and cycling. As can be seen from the data in the table, the battery production qualification rate is as high as 90%, which is far better than the 50%~60% of the comparative example.
[0077] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention; therefore, this means that all such substitutions and modifications that fall within the scope of the present invention are included in the appended claims.
Claims
1. A polymer for encapsulation, characterized in that, The encapsulation polymer is obtained by polymerizing reactive monomers and then modifying it with chlorination. The reaction monomers include isobutylene and vinyl lithium salt compounds.
2. The encapsulation polymer according to claim 1, characterized in that, The vinyl lithium salt compounds include lithium styrene sulfonate and / or lithium vinyl sulfonate.
3. The encapsulation polymer according to claim 2, characterized in that, Includes at least one of the following features (1) to (4); (1) The mass ratio of the lithium styrene sulfonate to the lithium vinyl sulfonate is 1:(0.2~2); (2) The mass of the isobutylene accounts for 80% to 90% of the mass of the reactant monomer; (3) The mass of the lithium styrene sulfonate accounts for 1% to 10% of the mass of the reactant monomer; (4) The mass of the lithium vinyl sulfonate accounts for 1% to 10% of the mass of the reactant monomer.
4. The encapsulation polymer according to claim 1, characterized in that, The chlorination modification includes treatment with a chlorinating agent; the chlorinating agent includes chlorine gas.
5. The method for preparing the encapsulation polymer according to any one of claims 1 to 4, characterized in that, Includes the following steps: The reactive monomers are mixed and polymerized. After the polymerization reaction is completed, post-treatment is performed, followed by chlorination modification to obtain the encapsulation polymer.
6. The method for preparing the encapsulation polymer according to claim 5, characterized in that, The polymerization reaction is carried out at a pressure of 0.5~1.5MPa and a temperature of 50~70℃.
7. The method for preparing the encapsulation polymer according to claim 5, characterized in that, The reaction conditions for chlorination modification are: pressure 0.05~0.3MPa, temperature 35~45℃, and time 10~30min.
8. A cell for a sulfide solid-state battery, characterized in that, The encapsulation polymer prepared by any one of the encapsulation polymers according to claims 1 to 4 or by any one of the encapsulation polymers according to claims 5 to 7 is coated onto the side of the battery cell for encapsulation.
9. The sulfide solid-state battery cell according to claim 8, characterized in that, The polymer solution used for encapsulation is prepared as a polymer solution with a mass concentration of 1% to 3% during coating.
10. A sulfide solid-state battery, characterized in that, Including the sulfide solid-state battery cell as described in claim 8 or 9.